Comparison of the Knowledge and Perception of Pharmacovigilance Among Pharmacy, Dental and Medical Students in Aden-Yemen - Alshakka, Mohammed; Bahattab, Owsan A; Ali, Heyam; Othman, Gamil; Ansari, Mukhtar; Shankar, Pathiyil Ravi; Ibrahim, Mohamed Izham Mohamed (Journal of Pharmacy Practice and Community Medicine)
Background: Adverse drug reactions (ADRs) represent a serious health problem. Despite all the benefits of modern medicines, evidence continues to mount that ADRs to them are common, yet often preventable cause of illness, disability and even death. ADRs are responsible for a significant number of hospital admissions. Healthcare professionals have an important role to play in reducing ADRs. Purpose: The goal of this study was to compare the knowledge and attitudes of pharmacy, dental and medical students regard¬ing adverse drug reactions (ADRs), as well as their perceptions of barriers to ADR reporting, in Aden University, Yemen. Methods A cross-sectional study was conducted among final-year students. A total of 130 pharmacy students, 101 medical and 69 dental students completed the self-administered questionnaire. The study was conducted from July 1 to October 31, 2016. The responses of pharmacy students were compared to those of dental and medical students. Results: The mean ages of the pharmacy, medical and dental students were 25.13 ± 1.90 years. A non-significant gender difference (P < 0.766) was found in the mean knowledge score of the participants, with female participants (n = 137) showing more knowledge of ADR reporting (4.66 ± 1.888) than their male counterparts (n = 163, 4.53 ± 1.857). Another important finding of this study was a significant difference (P < 0.001) between pharmacy, medical and dental students withknowledge about ADR reporting, with pharmacy students showing a greater degree of knowledge (5.23 ± 1.75) about ADR reporting than medical students (3.78 ± 1.61) with the dental students knowledge being intermediate (4.43 ± 2.02). Conclusion: The results indicate that pharmacy, dentistry and medical students demonstrated lack of understanding knowledge about ADRs. Final-year pharmacy students exhibited more knowledge about ADRs and showed more positive attitudes regarding their capacity to handle and report ADRs than a fi¬nal-year medical and dental students.
Keywords: Aden; dental; Pharmacy; Medical; Students; Pharmacovigilance; Comparison; Yemen